ANALISIS KUALITAS WEBSITE PERPUSTAKAAN FAKULTAS TEKNIK UNIVERSITAS NEGERI GORONTALO - Ryan Loanardo; Moh. Hidayat Koniyo; Lillyan Hadjaratie (Diffusion: Journal of Systems and Information Technology, 2022)
Abstract  The research aimed to determinate the user satisfaction score on the quality of a library website and identify the factors affecting the quality of a library website. In this research, the researcher carried out observation, literature study related to the research topics and questionnaire as the data collection methods. The population of this research was the public who have utilized the library website, specifically at the Faculty of Engineering. In addition, the sampling employed a Webqual 4.0 method where the number of samples were 57. Respondents taken for two week. The website evaluated in this research was the library website at the Faculty of Engineering. The research finding proved that all the proposed model variable affect user satisfaction. The variable with the highest score in influencing the library website user satisfaction was Service Quality. Meanwhile, Information and Usability Quality were variables that remain to be improved to enhance user satisfaction. Keywords: Quality of Website, Webqual 4.0, Content, Library . Abstrak Penelitian ini bertujuan untuk mendapatkan nilai kepuasan pengguna dan  mendapatkan faktor-faktor yang mempengaruhi kualitas website perpustakaan .  Untuk  menunjang  penelitian,  peneliti  melakukan  observasi,  studi  literatur sejenis, dan kuesioner sebagai metode pengumpulan data. Populasi pada  penelitian ini adalah masyarakat umum yang telah menggunakan website perpustakaan,   khususnya   di Fakultas Teknik.   Pengambilan   sampel   dilakukan   dengan   metode Webqual 4.0. Terkumpul 57 responden yang  menjadi sampel pada penelitian ini setelah 2 (dua) minggu masa pengumpulan data.  Website yang dimaksud pada penelitian ini adalah perpustakaan Fakultas Teknik. Hasilnya, seluruh  variabel  pada  model  yang  diajukan  terbukti  berpengaruh  pada  pembentukan  kepuasan pengguna. Variabel dengan nilai tertinggi dalam pembentukan kepuasan  pengguna website perpustakaan adalah Service Quality. Information  dan Usability Quality menjadi variabel yang perlu ditingkatkan sehingga kepuasan  pengguna dapat terbentuk lebih baik Kata Kunci : Kualitas Website, Webqual 4.0 , Konten, Perpustakaan